The collateral frameworks of the Eurosystem, the Federal Reserve System and the Bank of England and the financial market turmoil - Samuel Cheun; Isabel von Köppen-Mertes; Benedict Weller (European Central Bank (ECB), 2009)
In response to the turmoil in global financial markets which began in the second half of 2007, central banks have changed the way in which they implement monetary policy. This has drawn particular attention to the type of collateral used for backing central banks' temporary open market operations and the range of counterparties which can participate in these operations. This paper provides an overview of the features of the different operational and collateral frameworks of three central banks that have been significantly affected by the crisis: the Eurosystem, the Federal Reserve System and the Bank of England. The paper describes the factors that shaped the three frameworks prior to the turmoil. It then describes the actions the three central banks took in response to the turmoil and analyses to what extent these actions were dependent on the initial design of the operational and collateral framework.
Keywords: E52; E58; G01; G20; 330; Collateral Framework; Central Bank Repo Auctions; Collateral; Open Market Operations; Financial Market Turmoil 2007-2009.